Cost Effective Negative Plenum Cleanroom for Microelectronic Engineering undergraduate - Uda, Hashim (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://www.unimap.edu.my/